Geothermal Energy Sources and Biogas Applications in Science - Siddikov Rasuljon Oktamovich; Mirzayev Islombek; Khusanova Sarvinoz; Bakhriddinova Dilnora (Academia One, 2023)
In this article, opinions were expressed about the application of biogas to science and geothermal energy
Keywords: biogas; electricity; heating; energy